Bypassing primary stroke centre reduces delay and improves outcomes for patients with large vessel occlusion. (June 2016) - Mohamad, Niwar Faisal; Hastrup, Sidsel; Rasmussen, Mads; Andersen, Mikkel Strømgaard; Johnsen, Søren Paaske; Andersen, Grethe; Simonsen, Claus Ziegler
Objective: In large-vessel occlusion, endovascular therapy is superior to medical management alone in achieving recanalisation. Reducing time delays to revascularisation in patients with large-vessel occlusion is important to improving outcome. Patients and methods: A campaign was implemented in the Central Denmark Region targeting the identification of patients with large-vessel occlusion for direct transport to a comprehensive stroke centre. Time delays and outcomes before and after the intervention were assessed. Results: A total of 476 patients (153 pre-intervention and 323 post-intervention) were included. They were treated with either intravenous tissue plasminogen activator or endovascular treatment (alone or in combination with intravenous tissue plasminogen activator). Endovascular therapy patients' median system delay was reduced from 234 to 185 min (adjusted relative risk delay 0.79 (95% confidence interval: 0.67–0.93)). The in-hospital delay was the main driver with an adjusted relative risk delay of 0.76 (confidence interval: 0.62–0.94), while pre-hospital delay was almost significantly reduced with an adjusted relative delay of 0.86 (confidence interval: 0.71–1.04). This was achieved without increasing the intravenous tissue plasminogen activator-treated patients' delay. Significantly more patients treated with endovascular therapy in the post-interventional period achieved functional independence (62% versus 43%), corresponding to an adjusted odds ratio of 3.08 (95% confidence interval: 1.08–8.78). Conclusion: Direct transfer of patients with suspected large-vessel occlusion to a comprehensive stroke centre leads to shorter treatment times for endovascular therapy patients and is, in turn, associated with an increase in functional independence. We recorded no adverse effects on intravenous tissue plasminogen activator treatment times or outcome.